SEMAR-SUDS : Sistem Drainase Cerdas dan Berkelanjutan Berbasis Sustainable Urban Drainage Systems sebagai Mitigasi Bencana Banjir di Kawasan Polder Tawang Semarang - Retsya Saputri; Valiensia Dian Permata Sari; Amalina Fildza Hafila; Rio Devilito (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Semarang City is an urban area with a high vulnerability to flooding. Based on data from the Semarang City Regional Disaster Management Agency, in 2022 there were 133 flood events with extreme rainfall reaching 200 mm per day. Kota Lama Semarang is a historical tourist destination with high heritage value, but this area often faces flooding challenges, especially around the Tawang Polder Area with inundation reaching 30-100 cm. This condition is triggered by an existing drainage system that is not optimal due to limited channel capacity and blockages caused by sedimentation. The purpose of this study is to develop the SEMAR-SUDs smart drainage system innovation. The writing method was carried out through literature studies, hydrometeorological data reviews, and descriptive-quantitative analyses, which formed the basis for the design and implementation of the innovation. SEMAR-SUDs (Semarang-Sustainable Urban Drainage Systems) concept is an integrative solution that combines three main elements Debris Separate Baffle Boxes (DSBB) as a technology for separating waste and sediment, ArborFlow technology based on ecodrainage that optimizes rainwater retention and distribution and Self Closing Flood Barriers that work automatically to protect critical areas. The implementation of SEMAR-SUDs can be a solution model in increasing flood disaster resilience in the city of Semarang while supporting the realization of SDGs 9 (sustainable infrastructure development), SDGs 11 (resilient and sustainable cities), and SDGs 13 (climate action). The SEMAR-SUDs innovation is highly suitable for implementation in Semarang City to mitigate flooding and realize a smart, adaptive, and sustainable drainage system infrastructure.